Contribution of prosthetic treatment considerations for dental extractions of permanent teeth - Miguel Ángel Fernández-Barrera; Carlo Eduardo Medina-Solís; Juan Fernando Casanova-Rosado; Martha Mendoza-Rodríguez; Mauricio Escoffié-Ramírez; Alejandro José Casanova-Rosado; José de Jesús Navarrete-Hernández; Gerardo Maupomé (PeerJ, 2016)
Background. Tooth loss is an easily identifiable outcome that summarizes a complex suite of factors in an individual’s history of dental disease and its treatment by dental services over a lifetime. Assessment of overall tooth loss data is essential for epidemiologically evaluating the adequacy of dental care provided at a systems level, as well as for placing in context tooth loss for non-disease causes. For example, when derived from prosthetic treatment planning, the latter may unfortunately lead to some teeth being extracted (pulled) for the sake of better comprehensive clinical results. The objective of the present manuscript was to identify the contribution to overall tooth loss, by extraction of permanent teeth because of prosthetic treatment reasons. Material and Methods. A cross-sectional study included sex, age, total number of extractions performed by subject, sextant (anterior vs. posterior), group of teeth (incisors, canines, premolars and molars), upper or lower arch, and the main reason underlying extraction (extraction for any reason vs. prosthetic treatment), in patients 18 years of age and older seeking care at a dental school clinic in Mexico. A multivariate logistic regression model was generated. Results. A total of 749 teeth were extracted in 331 patients; 161 teeth (21.5% of total) were extracted for explicit prosthetic treatment indications. As age increased, the likelihood of having an extraction for prosthetic reasons increased 3% (OR = 1.03, p < 0.001). Women (OR = 1.57, p < 0.05) were more likely to be in this situation, and molars (OR = 2.70, p < 0.001) were most at risk. As the total number of extractions increased, the risk of having an extraction for prosthetic reasons decreased (OR = 0.94, p < 0.05). Conclusions. A significant amount (21.5%) of the extractions of permanent teeth were performed for prosthetic reasons in this dental school clinical environment; age, sex, type of tooth, and the total number of extractions moderated such pattern.